Association between handgrip strength and hypertension in children and adolescents: an analysis of the National Health and Nutrition Examination Survey 2011–2014 - Li, Huanhuan; Gu, Hongmei (Frontiers in Pediatrics, 2025)
AimHandgrip strength (HGS), a measure of muscle strength, has been reported to be associated with the risk of hypertension in adults. This study intended to assess the relationship of relative HGS (rHGS) and HGS asymmetry ratio with elevated blood pressure and hypertension in children and adolescents.MethodsThis cross-sectional study included children and adolescents aged 6–19 years with HGS and blood pressure measurements in the 2011–2014 National Health and Nutrition Examination Survey (NHANES) dataset. The relationships of rHGS and HGS asymmetry ratio with elevated blood pressure and hypertension were assessed using weighted logistic regression models and described as odds ratio (OR) with 95% confidence interval (CI). Subgroup analysis was conducted according to age (<13, ≥13 years) and gender (male, female).ResultsIn total, 3,736 children and adolescents were included in the study, of whom 509 (13.75%) had elevated blood pressure and 188 (4.72%) had hypertension. High rHGS levels were related to lower odds of elevated blood pressure (OR = 0.52, 95%CI, 0.33–0.81) and hypertension (OR = 0.34, 95%CI, 0.18–0.66). In addition, children and adolescents with HGS asymmetry ratio of >30.0% had higher odds of elevated blood pressure (OR = 2.14, 95%CI, 1.27–3.61) and hypertension (OR = 3.02, 95%CI, 1.42–6.42). Subgroup analyses demonstrated that the relationship between high rHGS levels and lower odds of elevated blood pressure and hypertension did not differ by age or sex, whereas the association between HGS asymmetry ratio of >30.0% and higher odds of elevated blood pressure and hypertension was found only in children ≥13 years and males.ConclusionHigh rHGS levels were associated with lower odds of elevated blood pressure and hypertension in children and adolescents, whereas an HGS asymmetry ratio of >30.0% was related to higher odds of elevated blood pressure and hypertension.